Accumulative extrusion bonding of Cu/Al bimetallic tubes: Design, fabrication, characterization, testing, and modeling - Matthew R. Standley; Marko Knezevic (Journal of Materials Research and Technology)
Accumulative extrusion bonding (AEB) is employed to bond bilayer Cu/Al tubes at room temperature for elucidating the quality of bonding, microstructure evolution, and strength characteristics. Bonding occurred at 68 % radial strain and further improved at 75 %, but did not occur at 52 %. After successful fabrication, the evolution of grain structure and crystallographic texture, as well as hardness, strength, and interface integrity were characterized. The interfaces were found to be well-bonded via peel tests. While steady-state bonding occurred independent of preferential crystal orientations at the interface, the evolution of grain structure in Al was substantially different from that in Cu. Grains in Cu remained large and were found severely elongated along the extrusion direction, while those in Al were refined and slightly elongated. The origins of such structural changes stemmed from recrystallization taking place in the Al microstructure as revealed by kernel-average-misorientation fields, while Cu retained the accumulated strain energy but fragmented. Characterization of the grain structure near the interface revealed the impact of scratch-brush preparation in forming the structures involved with bonding. AEB induced local shear texture evolution owing to the severe straining as predicted using finite element simulations of the process at both 68 % and 75 % deformation conditions. As a result of severe microstructural changes, the hardness and strength of the Cu/Al tubes increased considerably over the respected initial annealed conditions. These results and insights from the results are presented and discussed.